A Possible Role of HMGB1 in DNA Demethylation in CD4+ T Cells from Patients with Systemic Lupus Erythematosus. (3rd September 2013) - Li, Yaping; Huang, Chenghui; Zhao, Ming; Liang, Gongping; Xiao, Rong; Yung, Susan; Chan, Tak Mao; Lu, Qianjin
Abstract : The aberrant activity of CD4 + T cells in patients with systemic lupus erythematosus (SLE) is associated with DNA hypomethylation of the regulatory regions in CD11a and CD70 genes. Our previous studies demonstrated that Gadd45a contributes to the development of SLE by promoting DNA demethylation in CD4 + T cells. In this study, we identified proteins that bind to Gadd45a in CD4 + T cells during SLE flare by using the method of co-immunoprecipitation and mass spectrometry, High mobility group box protein 1 (HMGB1) is one of identified proteins. Furthermore, gene and protein expression of HMGB1 was significantly increased in SLE CD4 + T cells compared to controls, and HMGB1 mRNA was correlated with CD11a and CD70 mRNA. A significant, positive correlation was found between HMGB1 mRNA and SLEDAI for SLE patients. Our data demonstrate that HMGB1 binds to Gadd45a and may be involved in DNA demethylation in CD4 + T cells during lupus flare.